2000
DOI: 10.1103/physreve.62.2566
|View full text |Cite
|
Sign up to set email alerts
|

Noise improves three-dimensional perception: Stochastic resonance and other impacts of noise to the perception of autostereograms

Abstract: Autostereograms can be perceived in different well-defined spatial levels. Therefore they are an excellent tool with which to examine spatiotemporal processes of multistable three-dimensional perception. We study properties of spatial ambiguity such as phase transitions between different spatial levels and hysteresis in perception with and without noise. We show that the perception of physical noise-which is added to the autostereograms in the form of a random dot pattern-is dependent on the perceived spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Our measurements, using an effective diffusion coefficient, are related to those using the more common measure of SR, the signal-to-noise ratio [8,21]. Considering that, in noisy systems like the brain, synchronization can be defined only in a statistical sense, as widely discussed in many articles and books [14,16,24,26], it is important to think in terms of fluctuations in synchrony, in addition to the more usual determination of the strength of the synchronization between brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our measurements, using an effective diffusion coefficient, are related to those using the more common measure of SR, the signal-to-noise ratio [8,21]. Considering that, in noisy systems like the brain, synchronization can be defined only in a statistical sense, as widely discussed in many articles and books [14,16,24,26], it is important to think in terms of fluctuations in synchrony, in addition to the more usual determination of the strength of the synchronization between brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate instantaneous phases past 42 Hz due to the limitations imposed by the sampling acquisition of our equipment and the requirements for a reliable interpretation of the operation done by the Hilbert transform [24]. This frequency range encompasses the most important physiological frequency bands, theta (4-8), alpha (8)(9)(10)(11)(12)(13)(14), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and gamma (>30 Hz). To summarize, the D eff calculation runs as follows: for a specific set of MEG signals, in the frontal lobe for example, (depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of subthreshold signal using noise has been proven in neural information process (Longtin, 1993;Nozaki et al, 1999;Stocks and Manella, 2001) and in data transmission fields (Barbay, 2001;Zozor and Amblard, 2003;Morfu et al, 2003;Comte and Morfu, 2003;Duan and Abbott, 2005) as well as information transmission in array of such coupled stochastic resonator (Lindner et al, 1998;Chapeau-Blondeau, 1999;Báscones et al, 2002;Morfu, 2003). Recent studies have also shown that noise can enhance image perception (Simonotto et al, 1997;Moss et al, 2004), autostereograms interpretation (Ditzinger et al, 2000), visual perception via eyes micro-saccade in retina (Hongler et al, (a) (b) (c)…”
Section: B Outlooks On Processing Applicationsmentioning
confidence: 99%
“…and then the signal detection ]. This effect known as Stochastic Resonance (SR), since its introduction to explain the periodic recurrence of ice ages in climate dynamics [Benzi et al, 1981;Benzi et al, 1983;Nicolis, 1982], has been investigated in many fields ] like visual perception [Simonotto et al, 1997;Ditzinger et al, 2000] or biology [Longtin, 1993;Gebeshuber, 2000;Zeng et al, 2000]. This phenomenon has been studied first in unicellular nonlinear systems, like the Schmitt trigger [Fauve & Heslot, 1983;Melnikov, 1993;Godivier & Chapeau-Blondeau, 1997;Gammaitoni et al, 1999], and more recently, considering lattices of coupled excitable cells [Lindner et al, 1995;Zhang et al, 1998;Locher et al, 1998;Lindner et al, 1998;Chapeau-Blondeau, 1999;ChapeauBlondeau & Rojas-Varela, 2000].…”
Section: Introductionmentioning
confidence: 99%